Ask and Ye Shall Receive? How Gender and Status Moderate Negotiation Success. (11th October 2013) - Amanatullah, Emily T.; Tinsley, Catherine H.
Abstract The backlash effect is a well‐documented negative social reaction toward women who are seen as violating gender norms because they engage in counterstereotypical (noncommunal, agentic) behaviors during the performance of their jobs. This social disincentive has been shown to account for women's diminished likelihood to initiate negotiations relative to men. But we question whether women who ignored this disincentive and initiated negotiations would even receive the resources they requested. We extend past research by showing women also incur financial penalties for initiating negotiations. This financial penalty can be explained by women's lower ascribed status relative to men's status and fortunately can be attenuated if women have achieved status. In two studies, we find consistent evidence that women who ask do not receive unless they have externally conferred status.